2015
DOI: 10.3855/jidc.7661
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of HIV patients with task-shifted primary care service versus routine hospital service in northern Thailand

Abstract: Introduction: Shifting the task of HIV care to primary care providers is an important strategy to sustain expanding access to antiretroviral therapy (ART) in high HIV burden countries like Thailand. In a pilot project, the task of following up ART-receiving patients was shifted from a physician-led HIV clinic team based at district level community hospital, to a nurse-led primary healthcare team of seven primary care centers, based at sub-district level in a district of Chiang Mai in northern Thailand. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…However, a systematic review on barriers and facilitators to lay health worker programmes found that while the community often had high levels of trust in lay workers, they also saw the care delivered by these workers as ‘insufficient’, particularly when they lacked access to medicines and equipment 47. Similarly, one Thai study reported that the community felt nurses based in local facilities delivered lower-quality care while also appreciating the benefit of not having to travel to hospital to receive treatment 68…”
Section: Resultsmentioning
confidence: 99%
“…However, a systematic review on barriers and facilitators to lay health worker programmes found that while the community often had high levels of trust in lay workers, they also saw the care delivered by these workers as ‘insufficient’, particularly when they lacked access to medicines and equipment 47. Similarly, one Thai study reported that the community felt nurses based in local facilities delivered lower-quality care while also appreciating the benefit of not having to travel to hospital to receive treatment 68…”
Section: Resultsmentioning
confidence: 99%
“…In Thailand, HIV-infected patients exposed to a nurse-led primary care service reported greater satisfaction with services than their counterparts who continued to be seen by physicians. 22 Iwu and Holzemer 23 reviewed studies of physician-to-nurse task shifting in HIV settings in Sub-Saharan Africa; they reported increased levels of job satisfaction, as indicated by feelings of stature, achievement, and morale among nurses in 3 studies. In Malawi, patients rated HIV prevention services more positively after the hospital workers (including physicians) received training in delivering peer-led HIV prevention interventions.…”
Section: Discussionmentioning
confidence: 99%
“…17,1921 Fewer studies have focused on the impact of task shifting on patient satisfaction with clinical services and the satisfaction of the lower-cadre workers with their new positions. 13,22,23 …”
Section: Introductionmentioning
confidence: 99%
“…Task-shifting HIV services to primary healthcare is an important strategy within this expansion of access to ART. [11], with a recent study in northern Thailand reporting greater accessibility and convenience for PLHIV receiving a task-shifted service at primary health care centers [12]. However, anecdotal evidence among healthcare professionals and policy makers has led to concern about the existence of HIV stigma in the communities where PLHIV reside.…”
Section: Introductionmentioning
confidence: 99%